A1_2 Moon Light - Hophuong, Ocean; Li, Leonard; Warford, Louis; Wu, Tong (Physics Special Topics, 2017)
Scientists appreciate a strong laser but for everyone else, what does a strong laser mean? In this article, we explore how strong of a laser is necessary to see some light from the Moon with the human eye on Earth. We use the luminance threshold of a human eye under ideal conditions to find a minimum power of 8.29 x 10^12 W. At this power, we have some unintended results and we must start considering the consequences of our assumptions.